Implementasi Kebijakan Program Keluarga Harapan Sebagai Upaya Pengentasan Kemiskinan di Kota Medan - Chairika Nasution; Kgs. M. Sobri; Azhar; Abdul Najib (PERSPEKTIF, 2023)
This study aims to analyze the implementation of the Family Hope (PKH) program policy as an effort to alleviate poverty in Medan City with an Implementation Theory approach according to Van Metter and Van Horn theory. The approach used in this study is a qualitative approach. The data collection techniques used are through observation, interviews, and documentation. Data analysis techniques according to Miles and Huberman offer a general pattern of analysis by following an interactive model carried out with the stages of data collection, data reduction, data presentation, and conclusions. The results of the research on the Implementation of the Family Hope Program (PKH) Policy as an Effort to Alleviate Poverty in Medan City can be said to be not optimal, according to the 6 variables that the author uses from Van Metter and Van Horn's theory, namely: (1) Size and Purpose The policy does not have mapping in implementing this program so there is still a misunderstanding between the implementers and the target recipients of this assistance. (2) Human resources are adequate, but the budget for distribution is still a problem, (3) Characteristics of implementing agents in accordance with SOPs (standard operating procedures) and tupoksi, (4) Communication between implementing organizations is still minimal in coordinating with other organizations. (5) The dispositional attitude of the Executors has supported and carried out their respective duties. (6) The social, economic and political environment is supportive so that it affects the beneficiaries.